IMPLEMENTASI PERAN JAKSA PENGACARA NEGARA DALAM MEMBANTU MASYARAKAT UNTUK MENYELESAIKAN PERKARA PERDATA DI KEJAKSAAN NEGERI BULELENG - Putra, I Komang Tri Mega Rastika; Dantes, Komang Febrinayanti; Dewa Bagus Sanjaya (Universitas Pendidikan Ganesha, 2025)
This research explains aims to (1) help provide understanding to the community in the Buleleng Regency regarding the duties and authority of State Prosecutor Lawyers in assisting the community to resolve civil cases and (2) assist in evaluating the performance of State Prosecutor Lawyers in providing civil legal assistance to the community. This research is an empirical and descriptive study, critically aimed at analyzing relevant legal facts and describing them in detail. The results of the research are (1) a lack of understanding about the duties and role of State Prosecutor Lawyers among the community leads to the ineffective implementation of Law Number 7 of 2021, especially regarding civil legal assistance provided by State Prosecutor Lawyers to the community. (2) Implementing Law Number 7 of 2021, State Prosecutor Lawyers encountered several obstacles such as the lack of community participation in consulting their civil issues with State Prosecutor Lawyers due to the community's ignorance about the legal assistance that State Prosecutor Lawyers can provide, thus the solution provided in this study is to increase socialization both directly and through electronic media such as television and radio. If the community has a better understanding of the legal assistance provided by State Prosecutor Lawyers, the result would be that the community finds it easier to resolve their civil issues and, of course, Law Number 7 of 2021, especially regarding the legal assistance that State Prosecutor Lawyers can provide to the community, can be effectively implemented for all segments of society in the Buleleng Regency.